Performance Assessment in Public Transportation Services: A Review of Research Approaches - Drissi El Bouzaidi, Chorouk; Jami, Jihad (European Scientific Journal, ESJ, 2025)
This article presents a thematic review of studies on public performance in public transport services. Based on a structured analysis of the literature, it explores five major areas: local governance of public services, public management, Delegation of public services management, Public performance steering and Public transportation performance. The aim is to identify the main approaches, key concepts and evaluation criteria used in these fields. A summary diagram of the review is provided to illustrate the links between the various themes addressed. Drawing on the results of the analysis, the article introduces an original interpretation model - the GMDP-TC model - which provides a better understanding of the determinants of performance in the context of public transport. This contribution aims to enrich thinking on improving public performance through better governance and more effective management of transport services.